Camaenidae (Snails) of Florida, Zachrysia provisoria, Caracolus marginellus (Mollusca: Pulmonata) - Kurt Auffenberg; Lionel A. Stange (EDIS, 2002)
This document is EENY-118 (originally published as DPI Entomology Circular No. 356), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: November 1999.